Valuation of Network Effects in Software Markets A Complex Networks Approach - Kemper, Andreas (Contributions to Management Science, 2010)
The customer base is an important value driver of software companies and a reliable prediction of its development is fundamental for investment decisions. A particularity in software markets is that an individual’s purchasing decision is often influenced by other users’ choices. Although such customer network effects are evident, their quantitative assessment remain elusive with conventional approaches. This book contributes to closing this gap by developing methods for measuring network effects and their implications for valuation in software markets. Based on the theory of complex networks the book reveals that such diffusion processes highly depend on structural properties of customer networks. Moreover, it depicts that such insights are contributions to improve the quality of valuations in software markets. But the implications of this research also comprise social and political aspects as they can be applied in order to prevent corporate failures in all network effect markets